Baghdad, the capital of the Arab Islamic state during the Abbasid era / Reasons for its location choice and continuity - Abdulhamid, Maha Asad Abdulhamid taha (Sulaimani Journal for Humanities, 2026)
The idea of choosing (Baghdad as a Capital of the Arab Islamic country in the Abyssinian era/ it's placement reasons and continuity) represents one of the fundamental historical phenomenon which the researchers should focus on it. Accordingly, the researcher dig deep on the reasons behind the features that had been carried by Baghdad, and motivated the Abyssinian Caliph Al-Mansour to make it as his own capital (and then the caliphs whom followed him as well) in spite of the moving away from it for some time and circumstances. So there were many political, economic, geographic, social reasons and many others (which would be discussed throughout the research). Herewith, the research studied the reasons and motivations depending on many selected references.
Keywords: Baghdad; political; economic; military and medical motivations